Stereotactic body radiation therapy planning for liver tumors using functional images from dual-energy computed tomography. (April 2020) - Ohira, Shingo; Kanayama, Naoyuki; Toratani, Masayasu; Ueda, Yoshihiro; Koike, Yuhei; Karino, Tsukasa; Shunsuke, Ono; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Highlights: This study proposes a functional image based SBRT planning for liver tumors. The normalized iodine density map from DECT showed strong correlation with FIB-4. The proposed method could reduce doses to the high functional liver volume. The target coverage was comparable with the standard clinical plan. Abstract: Purpose: This study aimed to generate a functional image of the liver using dual-energy computed tomography (DECT) and a functional-image-based stereotactic body radiation therapy plan to minimize the dose to the volume of the functional liver ( V fl ). Material and methods: A normalized iodine density (NID) map was generated for fifteen patients with liver tumors. The volume of liver with an NID < 0.46 was defined as V fl, and the ratio between V fl and the total volume of the liver (FLR) was calculated. The relationship between the FLR and Fibrosis-4 (FIB-4) was assessed. For patients with 15% < FLR < 85%, functional volumetric modulated-arc therapy plans (F-VMAT) were retrospectively generated to preserve V fl, and compared to the clinical plans (C-VMAT). Results: FLR showed a significantly strong correlation with FIB-4 ( r  = −0.71, p  < 0.01). For ten generated F-VMAT plans, the dosimetric parameters of D99%, D50%, D1% and the conformity index were comparable to those of the C-VMAT ( p  > 0.05). For V fl, F-VMAT plans achieved lower V5Gy (122.4 ± 31.7 vs 181.1 ± 57.3 cc), V10Gy (44.4 ± 22.2 vs 98.2 ± 33.3 cc), V15Gy (22.6 ± 20.3 vs 49.8 ± 33.7 cc), V20Gy (11.6 ± 14.1 vs 24.9 ± 25.1 cc), and D mean (3.9 ± 2.3 vs 5.8 ± 3.0 Gy) values than the C-VMAT plans ( p  < 0.01). Conclusions: The functional image derived from DECT was successfully used, allowing for a reduction in the dose to the V fl without compromising target coverage.